TINJAUAN BIMBINGAN DAN KONSELING TERHADAP PERILAKU TAWURAN PELAJAR SMK DI JAKARTA PUSAT - Dody Riswanto; Syifa Jauhar Nafisah; Veno Dwi Krisnanda; Assyifa Diya Addin (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The general aim of this study is to examine the fighting behavior of vocational high school students in Jakarta from the perspective of Guidance and Counseling. The specific aim of this study is to provide education and recommendations, particularly to schools, on how to handle cases of student fights in vocational high schools. The research method used is qualitative, with data collection techniques including observation, document studies, and audiovisual information. The data analysis employed several procedures, namely verifying data validity through triangulation techniques, synthesizing, analyzing, interpreting data, and drawing final conclusions in the form of propositions. The results and discussion of the study are: 1) brawls are caused by the immature psychological and mental condition of vocational high school students; 2) students have difficulty finding their own identity, ultimately choosing brawls as a form of self-expression; 3) strong friendship solidarity, where solidarity serves as a sense of strong unity; 4) social environment validation, where students need recognition to be well accepted within their peer group; 5) parenting patterns, where parents have great difficulty controlling and supervising their children's activities.